Queer migrations: Sexuality, U.S. citizenship, and border crossings - Luibhéid, Eithne; Cantú, Lionel (University of Minnesota Press, 2005)
À l’intersection de la citoyenneté, de la sexualité et de la race, une nouvelle perspective sur l’expérience immigrante Queer Migrations rassemble des chercheurs pour fournir des analyses des normes, des institutions et des discours qui affectent les immigrant.e.s queer de couleur, et propose également des études ethnographiques sur la façon dont ces nouvelleaux arrivant.e.s ont transformé les communautés d'immigrant.e.s établies à Miami, San Francisco et New York. Contributeurices : Martin F. Manalansan IV, Susana Peña, Erica Rand, Timothy Randazzo, Horacio N. Roque Ramírez, Alisa Solomon, Siobhan B. Somerville, Alexandra Minna Stern.
Keywords: amériques; approches et analyses; identités LGBTQIA2+; outils; ouvrages de références; queer; racisme; ressource en ligne; régions géographiques; sexisme; système colonial; systèmes d'oppressions; états-unis

The Black studies reader - Bobo, Jacqueline; Hudley, Cynthia; Michel, Claudine (Routledge, 2004)
Black studies emerged from the tumultuous social and civil rights movements of the 1960s and empowered African Americans to look at themselves in new ways and pass on a dignified version of Black history. However, it also enriched traditional disciplines in profound and significant ways. Proponents of Black and ethnic studies confronted the false notion that scholarly investigations were objective and unbiased explorations of the range of human knowledge, history, creativity, artistry, and scientific discovery. As they protested against hegemonic notions like universal psychology and re-evaluated canonical texts in literature, a new model of academic inquiry evolved: one committed to serving a range of populations, that critiqued traditional politics, culture, and social affairs, and worked with activist energy for the transformation of the existing social order. With an all-star cast of contributors, The Black Studies Reader takes on the history and future of this multi-faceted academic field. Topics include Black feminism, cultural politics, Black activism, lesbian and gay issues, African American literature and film, education, and religion. This authoritative collection takes a critical look at the current state of Black studies and speculates on where it may go from here.
Keywords: LGBTQIA2+; afro-féminisme; amériques; approches et analyses; féminisme islamique; histoire et politique; identités LGBTQIA2+; militance; outils; ouvrages de références; racisme; ressource en ligne; régions géographiques; sexualité; système colonial; systèmes d'oppressions; thématiques; états-unis